2010
DOI: 10.1093/jmcb/mjq008
|View full text |Cite
|
Sign up to set email alerts
|

Wnt1-cre-mediated Conditional Loss of Dicer Results in Malformation of the Midbrain and Cerebellum and Failure of Neural Crest and Dopaminergic Differentiation in Mice

Abstract: The involvement of microRNAs (miRNAs) in the development of the neural crest (NC) cells and other neuronal differentiation is still poorly understood. Here, we investigated the global function of miRNAs in embryonic development by examining the Wnt1-cre-mediated Dicer knockout mice. Dicer ablation resulted in malformation of the midbrain and cerebellum and failure of NC and dopaminergic differentiation. First, the Dicer mutant fetuses exhibited dramatic malformation of the tectum and cerebellum and the eyelids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 68 publications
13
133
1
Order By: Relevance
“…Using a mouse with loss of neural crest-derived tissue, we have shown that the neural crest cartilage is needed for the formation of the mesodermally derived stapedial footplate, and in the absence of neural crest cartilage the oval window does not form correctly. In the Wnt1cre-Dicer mice, neural crest cells are able to migrate and are found within the same locations as in control littermates at E11 (Zehir et al, 2010), but cells do not differentiate into cartilage but undergo apoptosis (Huang et al, 2010;Zehir et al, 2010). It is possible, therefore, that the migrating neural crest cells at E11 are able to signal to the otic capsule, positioning the oval window before stapes differentiation.…”
Section: Neural Crest Part Of the Stapes Is Needed For Formation Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a mouse with loss of neural crest-derived tissue, we have shown that the neural crest cartilage is needed for the formation of the mesodermally derived stapedial footplate, and in the absence of neural crest cartilage the oval window does not form correctly. In the Wnt1cre-Dicer mice, neural crest cells are able to migrate and are found within the same locations as in control littermates at E11 (Zehir et al, 2010), but cells do not differentiate into cartilage but undergo apoptosis (Huang et al, 2010;Zehir et al, 2010). It is possible, therefore, that the migrating neural crest cells at E11 are able to signal to the otic capsule, positioning the oval window before stapes differentiation.…”
Section: Neural Crest Part Of the Stapes Is Needed For Formation Of Tmentioning
confidence: 99%
“…For this, we took advantage of the Wnt1cre/Dicer mouse, which has been shown to lack cartilages of neural crest origin, including the stapes (Huang et al, 2010). In these mutants, migration of crest into the head appears normal, but the cells do not differentiate into cartilage and high apoptosis is observed in the mandible mesenchyme at E12.5 (Huang et al, 2010;Zehir et al, 2010). At E18.5, in the wild-type mouse the middle ear ossicles can be seen strongly stained with Alcian blue (Fig.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…Recent studies have revealed the importance of miRNA expression in neural development and differentiation. For instance, it has been reported that Dicer-deleted mice exhibit malformations of the midbrain and cerebellum and failure of neural crest and dopaminergic differentiation (5). In addition, three brain-specific miRNAs (miR-124a, miR-9, and miR-132) have been proposed to regulate the transcription factor REST that mediates neuronal identity (6), and miR-132 seems also to be involved in the control of neuronal morphogenesis by decreasing the GTPase-activating protein, p250GAP (7).…”
Section: Micrornas (Mirnas Mirs)mentioning
confidence: 99%
“…In terms of tumor biology therefore, the loss of TFAP2A expression observed in invasive breast cancer is likely to contribute to tumorigenesis irrespective of whether the tumor cells express neural crest cells has recently been shown to abolish AP-2α expression in the sympathetic neurons of the mutant mice. 23 To investigate the role played by TFAP2A in CDKN1A induction in drug-treated MCF10A, cells were transfected with either non-silencing siRNA or the TFAP2A-specifc siRNA and were subsequently treated with either HU or vinblastine, or left untreated as controls. Monitoring mRNA levels revealed that TFAP2A-silencing again significantly reduced CDKN1A expression-both the constitutive, background levels seen in untreated cells but particularly the induced expression in drug-treated cells (see Fig.…”
mentioning
confidence: 99%